Transcatheter mitral valve implantation in the ongoing structural heart revolution. Issue 6 (27th March 2022) - Sá, Michel Pompeu; Ramlawi, Basel; Gray, William A.; Malin, John H.; Van den Eynde, Jef; Sicouri, Serge; Torregrossa, Gianluca; Klein, Christoph; Heil, Emanuel; Sündermann, Simon H.; Emmerich, Anna; Kempfert, Jörg; et al.
ABSTRACT: Transcatheter mitral valve implantation (TMVI) has emerged as a less invasive approach potentially surmounting some of the current hurdles associated with transcatheter edge‐to‐edge repair and high‐risk mitral valve surgery. In this review, we aimed to outline the main scenarios in the TMVI field, highlight current and upcoming devices, and describe challenges and clinical results. Finally, we briefly discuss the future perspectives for this emerging field and how TMVI might further advance the field of transcatheter treatments of mitral valve disease.